MULTIMEDIA DEVELOPMENT ON SPORTS HEALTH SUBJECT FOR THIRD SEMESTER STUDENTS OF PENJASKES FKIP UNSRI - HARTATI HARTATI; DESTRIANA DESTRIANA; SILVI ARYANTI (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of the research is to develop the results of software learning in the form of Compact disc (CD) for sports health effort lectures. Interactive CD is expected to be used to handle learning limitation adversity and to help students understanding the subject and improving appreciation, motivation, and independence. This study is a developmental research. The method used in this study is descriptive procedural where product development follows the procedures to produce a product. There are three basic steps that must be taken by the lecturer of the sports health subject; issue conceptualization, product making, and product trials. The study population is third semester students in physical education and health (Penjaskes) major that take the Sports Health course, Indralaya class. The method used in this research is statistics descriptive in analyzing the final result data. This research is to produce CD that can be used for teaching and learning in Penjaskes FKIP Unsri. The products which developed in CD are (1) teens’ RH, (2) environtmental health, (3) healthy life style and the effect of smoking, drinking, and drug abuse, (4) healthy eating behavior and balanced menu concept.